INNOVATION POLICY THROUGH THE LENS OF ECONOMIC THEORY - PIDORYCHEVA, Iryna (Journal of European Economy, 2023)
The paper comprises a comparative analysis of provisions of neoclassical, institutional, neo-Schumpeterian economic theories and the developmental tradition in terms of reasons for and limits to the government interventions into innovation. The theory behind the innovation policy has been improved and systemized in accordance with these economic approaches, creating a firm foundation for scientifically substantiated choices of political tools aimed at solving problems in innovation and eliminating their causes. Research results highlight that any choice of political tools must take into account recommendations of various economic theories and the features of the specific country, i.e., whether it is developed or developing, post-industrial, industrial or agrarian, its culture and history, economic and political circumstances etc. Theoretical arguments serve as the substantiation for proposals on the need to reconceptualize the support network and innovation incentives in Ukraine. JEL: О30, О31, O38.